The impact of integrating the ISO/IEC 25010 standard into the "PSG Balita" on the quality of the toddler nutritional status report data - Agus Hendra Al Rahmad; Junaidi Junaidi; Nunung Sri Muliyani; Emilda Emilda (AcTion: Aceh Nutrition Journal, 2023)
Utilizing Android-based Information Communication Technology (ICT) is pivotal in the healthcare sector for monitoring the growth, development, and assessment of nutritional status and ensuring enhanced data quality for toddlers. The adherence to ISO/IEC 25010 standards is imperative in developing high-quality applications like "PSG Balita." This study aimed to assess the impact of the "PSG Balita" Android application, which complies with the ISO/IEC 25010 standard, on the accuracy of nutritional status data for toddlers. In 2021, a quasi-experimental design research was conducted in Banda Aceh City, with the participation of 30 nutritionists from health facilities. The data were gathered by observations and interviews, utilizing a questionnaire that assessed the aspects of timeliness, completeness, accuracy, and usefulness. The intervention involved a one-month training session utilizing the "PSG Balita" software, which is consistent with the ISO/IEC 25010 standard. Data analysis utilizing repeated-measures ANOVA indicated that the "PSG Balita" application conformed to IEC standards, demonstrating a data quality score of 82,5. The intervention greatly improved the quality of data on the nutritional condition of children under the age of five (p < 0,05). In conclusion, the "PSG Balita" application, which is based on Android and adheres to ISO/IEC 25010 standards, can improve the precision of nutritional status data for toddlers, assessed in terms of timeliness, completeness, accuracy, and usefulness.Keywords: